Serum antibodies reactive with non-human primate retroviruses identified in acute onset schizophrenia - Lillehoj, Erik P.; Ford, Glen M.; Bachmann, Silke; Schröder, Johannes; Torrey, Edwin F.; Yolken, Robert H. (Journal of neurovirology, 2009)
Schizophrenia is a pervasive neuropsychiatric disease of uncertain etiology. Previous studies have postulated that retroviruses may contribute to the etiology of some cases of schizophrenia. We examined the possible relationship between retroviral infection and schizophrenia by measuring antibodies to a number of different primate retroviruses in the sera of individuals undergoing their first hospitalization for this disease. Sera from patients with first onset schizophrenia and matched healthy controls were analyzed by immunoblot and enzyme linked immunosorbent assays using purified retrovirus antigens to identify and quantify antibodies reactive with retrovirus proteins. A significantly increased incidence of antibodies reactive to gag encoded proteins of Mason-Pfizer monkey virus (MPMV), baboon endogenous virus (BaEV) and simian retrovirus type 5 (SRV-5) was observed in the sera of schizophrenia patients compared to controls. The reactivity of the cases and controls displayed the greatest differences in terms of antibodies to the proteins of Mason-Pfizer monkey virus. Employing an algorithm of enzyme linked immunosorbent assay reactivity followed by immunoblot confirmation, we found that MPMV antibodies in 28.9% of the individuals with first episode schizophrenia patients as compared to 3.7% of the unaffected controls (P < 0.009, Fisher's Exact Test). These studies are consistent with the occurrence of retrovirus replication in some individuals who are undergoing their first episode of schizophrenia.
Published online: 10 Jul 2009
Gesehen am 07.12.2020